Stale seedbed techniques for management of weedy rice (Oryza sativa f spontanea L.) in direct seeded rice - M., Ameena (Annals of Agricultural Research, 2016)
Weedy rice (Oryza sativa f spontanea) is a weedy form of cultivated rice which has recently emerged as a serious threat to the direct seeded kharif rice in Kerala. It competes aggressively with the crop, leading to drastic yield reduction besides contaminating the produce and the field. Considering the severity of the problem, field experiments were laid out to evolve an effective management strategy for weedy rice through integrated approach involving stale seedbed with herbicides and ploughing operations in a heavily weedy rice infested farmers’ field. The treatments comprised of 4 different types of stale seed bed (SSB) technique, viz. SSB with and without stimulatory rice crop and destruction with a total weed killer viz. glyphosate or paraquat followed by dry or wet ploughing. The studies revealed that sowing of rice seeds have no significant influence in stimulating germination of weedy rice. In general, stale seedbed treatments resulted in reduction in weedy rice plant density to the tune of 39.83 % to 63.72% during first year and 58.27 to 76.99% during second year. Stale seedbed coupled with glyphosate application followed by wet ploughing the field and wet seeding recorded the lowest weedy rice population and highest rice yields of 1.70 and 1.71 t/ha during both the years. Yield loss under unweeded situation measured by weed index was 75.60 with a BCR of 0.87 during first year and yield loss touched its peak during second year with a BCR of 0.70 which indicated the harmful effect of seed bank accumulated during previous year in unweeded areas. Stale seedbed with glyphosate application followed by wet ploughing under continuous submergence could be recommended as an effective preventive management strategy for weedy rice management in direct seeded rice.